ANALYZING THE STUDENTS' CREATIVE CHARACTER IN ELEMENTARY SCHOOL - Dhita Fransisca; Aswadi Jaya; Mega Prasrihamni (Universitas PGRI Palembang, 2024)
The aim of this research is to find out how the Pancasila student profile is implemented in forming the creative character of class IV students at SDN 54 Prabumulih. The method used in this research is qualitative method. The instruments used in this research were a list of interview questions and observations. Based on the results of the analysis, it can be concluded that the implementation of the Pancasila student profile in forming the creative character of class IV students at SDN 54 Prabumulih is categorized as very good, it can be seen that the students in the class have very good creative character when learning takes place, students are able to express many ideas such as when working on something. project by making a product and producing a work in the form of a piggy bank, where the students proposed their idea by only putting a hole in the bottom of the piggy bank so that the piggy bank doesn't look like a piggy bank when displayed, then the students also asked a lot about things that were new or that hadn't been done yet. they understand, and students are able to come up with new expressions or solve a problem in a way that the teacher had not thought of.